Exporting creative and cultural products: Birthplace diversity matters!. (15th April 2018) - Orefice, Gianluca; Santoni, Gianluca
Abstract: This paper analyses the effect of birthplace diversity on exports of creative and cultural goods, for 19 OECD countries, over the period 1990–2010. By matching UNESCO's creative and cultural exports classification to trade and migration data, we find a strong positive effect of birthplace diversity on the export of creative products. In particular, a 10% increase in the birthplace diversity index implies a 4% increase in creative goods exports. These results are robust across several specifications and shed light on a potential new channel through which migrants can contribute to the host country's export performance. It is interesting to note that only diversity of secondary and tertiary educated immigrants contributes to an increase in exports of creative and cultural goods. An instrumental variables approach addresses the potential endogeneity problems and confirms our results.